Ant Diversity (Hymenoptera: Formicidae: Myrmicinae) in Three Housing Types in Bandar Lampung - Ahmad Fauzi Rosnadi; Dwijowati Aji Saputri; Marlina Kamelia (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Bandar Lampung City has a population of 1.051.500 people with a density of 3.308,4 people/km2 in 2018. The population is densely accompanied by residential developments, one of which is housing. Housing in the city of Bandar Lampung amounted to 220 housing estates in 2018 consisting of types 21, 36, 45.54, and 70. Rapidly increasing development certainly affected the surrounding ecosystem. The ant is one indicator of change in the environment. Therefore it is important to research the identification of Myrmicinae ants in three types of housing in Bandar Lampung City. The research was conducted in November - October 2018. This type of research is quantitative with survey methods. The housing of each type is selected by random sampling then ant samples are taken using the standardized transect method. Two transects were installed in the yard of the house and a roadside transect. The ants obtained were identified using photographs, images and the key of determination. The results showed that there were 5 species of Myrmicinae from 3 genera namely Solenopsis geminata, Solenopsis invicta, Solenopsis molest, Tetramorium sp., and Monomorium sp. The most dominant subfamily Formicidae habitats are in the house and terrace house.